Konseling Realita untuk Meningkatkan Tanggung Jawab Belajar Siswa - Bariyyah, Khairul; Hastini, Rita Putri; Wulan Sari, Eva Kartika (Universitas Negeri Padang, 2018)
The responsibility of learning is a students ' awareness about their duties that must be implemented in order to meet the learning needs, while learning responsibility include tasks with a trustworthy, Independent and able to take responsibility over their duties to achieve an optimal award. The phenomenon that researchers has found to show some students have a low learning responsibility. The purpose of this study was to test the effectiveness of reality counseling to enhance the students ' responsibility. This study uses a pre-experimental design with the kind of One Group Pre-test and post-test. Subjects in this study were 5 students. This research instrument using a scale liable student learning and counseling guidelines reality. The data analysis technique used is Wilcoxon's Signed Rank Test . Counseling reality effectively to improve student learning responsibility. The results of post-test students in completing the learning responsibility scale after treatment is greater than or increased from the pre-test (17.05 pre-tests and post-test is 22.85 ). Wilcoxon tests results showed the Sig . (2-tailed ) was 0.042 <0.05 its means the reality counseling effective to improve student learning responsibility